Making sacrifices: how ungenerous gifts constitute jobseekers as scapegoats. Issue 2 (3rd May 2016) - Boland, Tom; Griffin, Ray
ABSTRACT: Although they are the recipients of welfare we argue that the unemployed are pathologized and scapegoated by the ungenerous nature of this gift. The suffering of the unemployed is explored here as emerging not from the lack of economic, psychological, and social goods, but from how gift-relations are imbued with power-relations, particularly as generated in activation policies currently spreading through the OECD. Inspired by theoretical consideration of Mauss, Girard, and others, we aspire to offer an imaginative rethinking of unemployment, moving beyond the simple notion that it is just a lack of work, to positioning unemployment as a foundational axis of punishment which is constitutive for modern society. In this way, the unemployed exist as imaginary scapegoats for political legitimization and as surplus labour which allows capitalism to function. Illustrative empirical data are drawn from interviews and media reportage in Ireland, where the switch to activation policies was made swiftly and dramatically since 2012.